EFEKTIVITAS PENDIDIKAN TERPADU DALAM MENINGKATKAN KAPASITAS DIRI: STUDI KASUS PENCEGAHAN BULLYING, PERGAULAN BEBAS, DAN PENYALAHGUNAAN NARKOBA: INTEGRATED EDUCATION IMPROVES SELF-DEVELOPMENT: A CASE STUDY OF PREVENTION OF BULLYING, RISKY SEXUAL BEHAVIOR, AND DRUG ABUSE - Indra Lesmana; Raden Bambang Sumarsono; Dedi Prestiadi; Endra Ubaidillah; Sasi Maulina; Mufti Nawang Prastiko (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Cases of bullying, promiscuity and drug abuse are forms of juvenile delinquency that are currently often occurring. These three cases certainly provide long-term risks that can affect students' psychological, physical, and emotional well, even the most extreme risk is pregnancy and transmission of sexually transmitted diseases. The purpose of this community service activity is to provide insight, knowledge, understanding, and increase the capacity of students in the context of the dangers of bullying, promiscuity, and drug abuse. A training approach based on socialization seminars is used in this community service activity. The community service activity was carried out at SMK Widya Dharma Turen involving 328 students in classes X and XI.  This community service activity is carried out through several methods used, including; (1) seminars; (2) presentation of materials; (3) awareness campaigns; (4) role play; (5) discussion; (6) problem-based learning (PBL), and (7) evaluation of pre-post test-based activities. The results of the pre-test and post-test will be analyzed using the t-test (difference test) assisted by the SPSS 24.0 program. The results of the activity showed an increase in student knowledge as seen from the comparison of pre-test and post-test scores. The average pre-test score of 65.76 increased to 73.81 in the post-test, with an improvement difference of 8.05. These findings show that the training provided is effective in increasing students' understanding and awareness of the negative impacts of bullying, promiscuity, and drug abuse. Thus, this service activity makes a positive contribution to prevention efforts.